Pengaruh Kepercayaan, Harga, Kualitas Produk Dan Kualitas Informasi Penggunaan Marketplace Terhadap Keputusan Pembelian Pada Marketplace Facebook (Studi Kasus Mahasiswa Universitas Islam Malang) - Muhammad Rizalul Mukhlis; Rois Arifin; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine the effect of trust, price, product quality and quality of information on using the marketplace on purchasing decisions on the Facebook marketplace (a case study on students at the Islamic University of Malang). The population in this study are consumers who have made purchases through the Facebook marketplace application within the campus of the Islamic University of Malang. The sampling technique used quantitative methods with a total sample of 85 respondents. The analytical method used is multiple linear regression analysis with SPSS application tools. The results of the study show that simultaneously the variables of trust, price, product quality and information quality influence purchasing decisions. Partially the variables of trust and product quality have an effect on purchasing decisions and the variables of price and quality of information partially have no effect on purchasing decisions because the significant value is greater than 0.05 and the t count <1.991. Keywords: Trust, Price, Product Quality, Information Quality